A narrativa do inimigo e a guerra civil como dispositivos biopolíticos de governo e controle de populações - Vilão, Carolini Dellavalle (Universidade do Vale do Rio dos Sinos, 2023)
The aim of this dissertation is to elucidate how the concept of enemy is a narrative constructed by those in power to legitimize an authoritarian government intervention against its citizens. In view of this, the problem question that is intended to be answered is: to what extent is the construction of a narrative about the enemy fundamental for the civil war to be a paradigm of government? By way of conclusion, the hypothesis raised will be confirmed, that is, that in current democracies the enemy's narrative is crucial to legitimize the legal civil war, which is a biopolitical device of control and that from it the State has more strength, while citizens lose their rights. In the first chapter, an analysis is carried out on the consequences of enmity in the legal system based on the thinking of Gunther Jokobs and later, the criticisms made to him by Raúl Zaffaroni are analyzed. It is important to understand in this problem who decides on the enemy and how he is recognized in society, this analysis is done through the study of Carl Schmitt's thought. In the second chapter, based on the thought of Giorgio Agamben, a study is made on how enmity legitimates the legal civil war and strengthens that exceptional practices enter the legal system. Finally, in the last chapter, it is clarified that the state of exception at its peak creates anomic spaces such as fields, which are updated in various ways in modernity. In addition, we present a study of the criticism made by Achille Mbembe to the concept of enmity, addressing how war has always occurred in the colonies and how the great “enemies” are currently individuals who have always been marginalized throughout history.” are currently individuals who have always been marginalized throughout history

Lo scopo di questa ricerca è chiarire come il concetto di nemico sia una narrazione costruita da chi è al potere per legittimare un intervento autoritario del governo contro i suoi cittadini. In considerazione di ciò, la domanda problema a cui si vuole rispondere è: in che misura la costruzione di una narrazione sul nemico è fondamentale perché la guerra civile sia un paradigma di governo? In conclusione, verrà confermata l'ipotesi sollevata, e cioè che nelle attuali democrazie la narrazione del nemico è cruciale per legittimare la guerra civile legale, che è un dispositivo biopolitico di controllo e che da essa lo Stato ha più forza, mentre i cittadini perdere i propri diritti. Nel primo capitolo si analizzano le conseguenze dell'inimicizia nell'ordinamento giuridico sulla base del pensiero di Gunther Jokobs e successivamente si analizzano le critiche mossegli da Raúl Zaffaroni. È importante capire in questo problema chi decide sul nemico e come viene riconosciuto nella società, questa analisi viene fatta attraverso lo studio del pensiero di Carl Schmitt. Nel secondo capitolo, basato sul pensiero di Giorgio Agamben, si studia come l'inimicizia legittima la guerra civile legale e rafforza l'ingresso di pratiche eccezionali nell'ordinamento giuridico. Infine, nell'ultimo capitolo, si chiarisce che lo stato di eccezione al suo apice crea spazi anomici come i campi, che si aggiornano in vario modo nella modernità. Inoltre, presentiamo uno studio della critica mossa da Achille Mbembe al concetto di inimicizia, affrontando come la guerra sia sempre avvenuta nelle colonie e come i grandi “nemici” siano attualmente individui che sono sempre stati emarginati nel corso della storia.
Keywords: Biopolítica; Estado de exceção; Inimigo; Stásis; Biopolitics; State of exception; Enemy; Stasis; Biopolitica; Stato di eccezione; Nemico; ACCNPQ::Ciências Humanas::Filosofia